The Senior Community Service Employment Program Its History and Evolution. A Report by the National Council on the Aging to the Chairman of the Select Committee on Aging. House of Representatives, One Hundredth Congress, Second Session. - Congress of the U.S., Washington, DC. House Select Committee on Aging; Congress of the U.S., Washington, DC. House Select Committee on Aging ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1988)
The Senior Community Service Employment Program (SCSEP)--now Title V of the Older Americans Act--evolved from Operation Mainstream, a pilot project established under Title II of the Economic Opportunity Act. Operation Mainstream, which was first funded in 1965, provided jobs for chronically unemployed, poor adults in a wide range of activities to improve the social and physical environment primarily in rural areas. Older adults were one of the target groups to be served by Operation Mainstream. Operation Mainstream's older worker component was converted from a pilot project into a national, ongoing program when the 1973 Older Americans Comprehensive Services Amendments became law. It was officially designated as the Older Americans Community Service Employment Act (Title IX of the 1973 Older Americans Comprehensive Services Amendments). Throughout its history, the SCSEP has served some of the most disadvantaged persons in society, particularly those with poverty incomes, limited education, and minority status. Numerous evaluations of SCSEP and its predecessor--the Mainstream Older Workers pilot project--have shown them to be very effective programs that should be retained and strengthened. (Author/KC)
Availability: Superintendent of Documents, Congressional Sales Office, U.S. Government Printing Office, Washington, DC 20402.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Community Services; Disadvantaged; Employment Programs; Federal Legislation; Federal Programs; Job Training; Minority Groups; Older Adults; Older Workers; Outcomes of Education; Program Effectiveness; Older Americans Act 1965 -- Senior Community Service Employment Program; Congress 100th; Reports, Descriptive